CLASSIFICATION OF INFORMATION FLOWS IN LOGISTICS: CLASSIFICATION OF INFORMATION FLOWS IN LOGISTICS - Kazakov, Stefan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The report presents a traffic study of information flows in logistics in a local area network built according to the 802.3 standard. The study of network performance is according to the number of computers in communication.